Developing a cooperative multicenter study in Latin America: Lessons learned from the Latin American Study of Nutrition and Health Project - Fisberg, Mauro (2017)
This report examines the challenges of conducting a multicenter, cross-sectional study of coun- tries with diverse cultures, and shares the lessons learned. The Latin American Study of Nutrition and Health (ELANS) was used as a feasibility study involving the most populous cities of eight countries in Latin America (Argentina, Brazil, Chile, Colombia, Costa Rica, Ecuador, Peru, and Venezuela) in 2014–2015, about 40% of the population of the Americas. The target sample included 9 000 individuals, 15–65 years of age, and was strati ed by geo- graphic location (only urban areas), gender, age, and socioeconomic status. Six principal challenges were identi ed: team structuring and site selections; developing a single protocol; obtaining ethic approvals; completing simultaneous eldwork; ensuring data quality; and extracting data and maintaining consistency across databases. Lessons learned show that har- monization, pilot study, uniformity of procedures, high data quality control, and communication and collaboration across sites are imperative. Barriers included organizational complexity, recruit- ment of collaborators and research staff, institutional cooperation, development of infrastructure, and identi cation of resources. Consensus on uniform measures and outcomes and data collection methodology, as well as a plan for data management and analysis, communication, publication, and dissemination of study results should be in place prior to beginning eldwork. While challeng- ing, such studies offer great potential for building a scienti c base for studies on nutrition, physical activity, and other health topics, while facilitating comparisons among countries.